Pedagogy of alternation and the implications of the process of becoming state-run in the educational practices of a family agricultural school in Piauí (Revista Contexto & Educação, 2023)
This work presents results of research undertaken with the objective of analyzing how the educational practices carried out in a Family Agricultural School located in the rural area of ​​Teresina - PI, based on assumptions of Pedagogy of Alternation, are articulated with the principles of Rural Education, before the process of the institution becoming State-run. Therefore, a qualitative descriptive research was carried out, whose data production procedures were: document analysis, semi-structured interview and questionnaire application. From the data analysis, it was found that the researched EFA uses some Pedagogy of Alternation tools, which facilitate teaching-learning, however, it is visible that the process of becoming State-run has weakened the performance of educational activities. The results also showed the students' empathy regarding the methodologies used by their teachers. It was concluded that, despite the difficulties, there are more proximity than differences between the principles of Pedagogy of Alternation developed by the EFA and those that rule Rural Education. Keywords: Rural Education. Teaching-learning. Differentiated Methodologies. Pedagogical tools.